Endocan serum concentration in uninfected newborn infants - Gabriela I Zonda; Radu Zonda; Andrei T Cernomaz; Luminita Paduraru; Bogdan D Grigoriu (Journal of Infection in Developing Countries)
Introduction: Endocan is a specific endothelial mediator involved in the inflammatory response. Its role in the diagnosis of sepsis has been studied in adult patients and late onset neonatal sepsis. The clinical signs of early onset sepsis (EOS) are nonspecific and routinely used biomarkers, such as C-reactive protein and procalcitonin, have low sensitivity, specificity and positive predictive value. Endocan could be useful as a biomarker for diagnosis of EOS, but at present normal range values for this molecule have not been reported. The aim of this study is to establish the normal values range for serum endocan in term and preterm newborns without risk factors for EOS and to characterize the variation pattern of its levels at different postnatal moments.